Dampak Evolusi Perlindungan Sosial Terhadap Kesejahteraan Sosial Dalam Perspektif Ekonomi Islam - Indah Fitriana Sari; Muhammad Rafi’i Sanjani (ITB AAS INDONESIA Surakarta, 2023)
Social protection is an important element and concept that reflects economic and social changes for the welfare of society. Social protection is defined as a program that prevents individuals from traveling in poverty. This social protection program will seek to provide protection and a sense of security to the community in order to achieve prosperity. Along with the efforts of Muslims to apply their religious teachings, there has been a study of welfare in the economy based on Islamic law. This research exists because Indonesia is still facing problems regarding welfare, where the state that should contribute to the welfare of its people is still far from expectations. Therefore, the purpose of this study is to see how the impact of changes in social protection promoted by the government on the social welfare of the community. This research uses a qualitative library research method with a normative approach. The results of this study are the change from social protection arises because the government wants to optimize the welfare of the community with various efforts, one of which is social services in the form of social security and social assistance which is expected to have an impact on the prosperity of life and the economy of the Indonesian people. Meanwhile, when viewed from the perspective of Islamic economics itself, basically economic welfare includes the welfare of individuals, society and the state. These three things will always be related to achieve optimal welfare.